Evaluation of the potential of unconventional energy resources in Peru Valle Chancay-Huaral - Carrasco, Maria del Carmen (1998)
The study area presents a shape that approximates that of a parallelogram, occupying 335,000 Ha., Having as limits by the north with the Huaura river basin, by the East with the Mantaro river basin coinciding with the continental watershed , by the South with the Chillón river basin and by the West with the Pacific Ocean.